2011
DOI: 10.1097/bpo.0b013e318209287d
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Radial Nerve Injury With Cannulated FixationofMedial Epicondyle Fractures in the PediatricHumerus

Abstract: IV, Case Series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The radial nerve’s localization has been the subject of much concern due to the potential for pathologic[1,2], traumatic[3,4], and iatrogenic[5-7] injuries. Radial nerve localization has been described relative to a distance from various bony landmarks: The acromion and lateral epicondyle[8] proximal to the elbow and the bicipital tuberosity distal to the elbow[9].…”
Section: Introductionmentioning
confidence: 99%
“…The radial nerve’s localization has been the subject of much concern due to the potential for pathologic[1,2], traumatic[3,4], and iatrogenic[5-7] injuries. Radial nerve localization has been described relative to a distance from various bony landmarks: The acromion and lateral epicondyle[8] proximal to the elbow and the bicipital tuberosity distal to the elbow[9].…”
Section: Introductionmentioning
confidence: 99%
“…1). During the initial operation, the mean age of the children was nine (median, 10.5; range, 6-14) in group A and 15 (16,(10)(11)(12)(13)(14)(15)(16)(17) years in group B. The mean follow-up was 10 (median, 11; range, 6-15) in group A and 10 (9.5, 5-15) years in group B.…”
Section: Methodsmentioning
confidence: 99%
“…Anakwe et al [31] reported delayed ulnar neuropathy after screw fixation in two patients, both of whom required a secondary procedure to decompress the ulnar nerve palsy, with complete recovery between 18 months and 2 years. Marcu et al [32] reported two cases of radial neuropathy, likely caused by the end of a threaded guide pin inadvertently advanced into anterolateral soft tissues.…”
Section: Operative Managementmentioning
confidence: 99%